2014
DOI: 10.18488/journal.58/2014.1.2/58.2.122.132
|View full text |Cite
|
Sign up to set email alerts
|

Small-Scale Milk Processing, Utilization and Marketing of Traditional Dairy Products in Bahir Dar Zuria and Mecha Districts, Northwestern Ethiopia

Abstract: This study was conducted to assess processing, utilization and marketing of traditional dairy products produced in Bahir Dar Zuria and Mecha districts in Northwestern Ethiopia. A single-visit-multiplesubject formal survey was conducted to collect data. A total of 150 households (75 households from each district) were individually interviewed using a semi-structured questionnaire. The major dairy products produced in the study area include butter, ghee, Ayib, Arera (defatted sour milk), Ergo (naturally fermente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
7
6
1
Order By: Relevance
“…The fermentation process is accomplished in 25 days during which its colour changes from white to light green (blue mold) and Metata cheese is now prepared for home consumption, sale and further storage for either consumption or medicinal uses (Figure 2). The present finding is more or less in line with the study conducted by [13] and [10] …”
Section: Purpose Of the Spices Powder Used In Ayib Makingsupporting
confidence: 94%
See 3 more Smart Citations
“…The fermentation process is accomplished in 25 days during which its colour changes from white to light green (blue mold) and Metata cheese is now prepared for home consumption, sale and further storage for either consumption or medicinal uses (Figure 2). The present finding is more or less in line with the study conducted by [13] and [10] …”
Section: Purpose Of the Spices Powder Used In Ayib Makingsupporting
confidence: 94%
“…About 32% -49% the respondents use gourd for storage of Metata cheese although some farmers use plastic containers and some uses both clay pot and plastic containers (Table 4). In general, the use of gourd, clay pot and plastic containers for storage of Ayib and Metata cheese types observed in the current study is in agreement with earlier report [10]; [13]; [15], which indicated that gourd (0%), clay pot (82.06%) and plastic (17.94%) in Bahir Dar Zuria and Mecha districts and gourd (47.13%), clay pot (27.63%) and plastic containers (11.6%) in Gondar and Dangila town of Amhara Regional state used for storage of Ayib and Metata cheese.…”
Section: Containers Used For Processing and Storage Ofsupporting
confidence: 93%
See 2 more Smart Citations
“…The use of unconventional veterinary inputs, clandestine purchase, non-compliance of waiting period, ignorance, or negligence of the rules of good hygiene practices, bad practices of trafficking, mismanagement of waste from mining and hospital sources, exposure of livestock feed on contamination and consumer perceptions are risky practices significantly affecting health animal status and sanitary quality of products of animal origin and rendering it unfit for human consumption. Previous studies in West Africa done by Savadogo et al [23], Boko et al [24], Coulibaly et al [25], KouamĂ©-Sina et al [6], Katinan et al [15], Bonfoh et al [26], Arohalassi et al [5], in East Africa by Yilma et al [27], Seifu [28], Seifu and Tassew [29], Ahmed et al [30], in South Africa by Beukes et al [31] and in North Africa by Aggad et al [32] mentioned that these practices contributed to contamination of milk with pathogenic germs and toxic substances, rendering it unfit for human consumption and therefore a danger to public health.…”
Section: Discussionmentioning
confidence: 99%